(3OejI GdbUQ hYUQI Cgd GdYUQs - (3GdHGNQRj , Ydj Hf GdMSf Hf Ydj Hf CHj GdWjH, CHh GdMSf,J (B467 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi eGeG CSHY ef CfYGeg s
(3BNQgG (B:s
(3NPgG fJjLI WHY Ef CgfJ Hg CLGH ai GdhbJ eKd GdYjf efaLQ JeJ OejI GdbUQ s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B81s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs